AN ANALYSIS OF MORAL VALUE AND DEIXIS IN SONG LYRICS “DYNAMITE” BY BANGTAN BOYS - Bella Safitri; Mundriyah Mundriyah (PROJECT (Professional Journal of English Education), 2024)
This article aims to find out the kind and dominant deixis found in the song lyrics of Bangtan Boys and to identify the moral value of song by Bangtan Boys for human’s life. The descriptive qualitative method was used to conduct this article. The data of this article were obtained by using documents and library research. The Source of data on this research was song lyrics from Bangtan boys namely “Dynamite”. Based on the results and discussion, the researchers deixis proposed deixis from Yule (1996) was found in BTS’s song lyrics. 56 data that contained deixis, included personal deixis is mostly found in 36 occurrences dominant in this song. The words are I, you, me, we, and my. Spatial deixis those are home, this, the city, and in the mirror which found in 7 occurrences. Temporal deixis is tonight, day or night, night, mortn, when and summer which are found in 13 occurrences. It can be concluded , in song lyrics “Dynamite”  the most dominant type used of deixis were personal deixis. The researchers founded 3 types of moral values from the song that are bravely, cooperativeness and thankfulness.  The researchers concluded that the moral values in song lyrics “Dynamite” by BTS was living life by doing the best and full of spirit.